Multi-metal-based oxide electrocatalyst as well as preparation method and application thereof
By mixing metal salts and specific organic ligands ultrasonic, combining rapid annealing technology to regulate crystal phase distribution, polymetal-based oxide electrocatalysts were prepared, solving the problems of high cost and slow kinetics of existing catalysts, and achieving efficient and stable oxygen evolution reaction performance.
Patent Information
- Application Number
- CN202411948559.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Due to the high cost of precious metal-based catalysts, low earth abundance and slow kinetics, existing oxygen evolution catalysts cannot be widely used in actual production, and the internal crystal structure of complex polymetal oxides obtained by conventional preparation methods cannot be adjusted, which affects catalytic performance and stability.
Ultrasonic mixing of five metal salt solutions and adding organic ligands containing specific substituents. After centrifugation, lyophilization, rapid heating, cooling, and grinding, the crystal phase distribution of the polymetal-based oxide is finally regulated by rapid annealing to prepare a polymetal-based oxide electrocatalyst with adjustable crystal structure, good conductivity and rich multi-stage structure.
This catalyst exhibits excellent activity and stability in the oxygen evolution reaction, has better overpotential than commercial IrO2 catalysts, and the LSV curve has no significant deviation after 5000 cycles of CV, which has good industrial application prospects.
Smart Images

Figure CN119736665A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a multi-metal-based oxide electrocatalyst and a preparation method and application thereof. Background Art
[0002] The acceleration of global industrialization, energy crisis and pollutants (SO x 、NO x The increase in emissions of carbon dioxide (CO2) and fine particulate matter (PM2.5 and 2.5 mmol / l) has expanded the public's demand for sustainable and clean energy. Among many new energy technologies, electrochemical hydrogen production has become one of the most promising technologies to replace fossil fuels due to its advantages such as environmental friendliness, zero carbon emissions, and high energy density. However, the practical application of water electrolysis technology is seriously hindered by the sluggish kinetics of the oxygen evolution reaction (OER). Therefore, it is necessary to develop efficient oxygen evolution catalysts to improve the reaction kinetics of OER. At present, most commercial oxygen evolution catalysts are precious metal-based catalysts, such as IrO2 and RuO2. However, these catalysts cannot be applied on a large scale in actual production due to their disadvantages such as low earth abundance, high cost, poor durability, and slow kinetics. Therefore, the development of efficient and low-cost non-precious metal OER catalysts is the key to the large-scale production of hydrogen production by water electrolysis.
[0003] Transition metal oxides are considered to be one of the most promising OER catalysts due to their abundant resources, simple preparation process, controllable structure and composition, and high stability. In recent years, researchers have conducted in-depth research on transition metal oxides and found that multi-metal oxides have higher catalytic activity and better stability than single metal oxides. This can be attributed to the fact that single metals have a fixed electronic structure, and their catalytic activity and the role of reaction intermediates are relatively simple. There is a synergistic effect between multi-metal atoms, with a larger electronic adjustable space and multiple active sites. Therefore, when participating in OER, multi-metal oxides show greater advantages. However, considering the interaction between the metals and the influence of thermodynamic factors, the internal crystal structure of the complex multi-metal oxides obtained by conventional preparation methods cannot be adjusted, and the dominant crystal planes cannot be fully exposed, which in turn affects the catalytic performance and stability of the catalyst, making it impossible to achieve large-scale industrial application.
[0004] Metal-organic frameworks (MOFs) are a new type of porous material composed of metal clusters or metal ions and organic ligands. Due to their strong adjustability, they have great application prospects. In addition, using MOF materials as sacrificial templates, a large number of MOFs derivatives with novel structures and excellent performance, such as metal oxides, can be synthesized, which opens up an effective way for the design of OER catalysts. Among them, by controlling the pyrolysis conditions of MOFs precursors or customizing organic ligands, efficient electrocatalysts can be obtained. Organic ligands are an important component of MOFs and a key factor in regulating the structure and performance of MOFs derivatives. Appropriate pyrolysis conditions can regulate the crystal structure distribution of MOFs derivatives and optimize the internal metal ion distribution to give full play to the synergistic effect between different metals and improve the catalytic activity of the material. Therefore, preparing multi-metal oxides using MOFs materials as precursors is an effective method to regulate the crystal structure distribution of multi-metal oxides. However, it is necessary to fully consider the type of organic ligands and the selection of pyrolysis conditions. Therefore, it is still facing great challenges to develop a simple and efficient technology to regulate the crystal structure distribution of multi-metal oxides so that they can be applied on a large scale. Summary of the invention
[0005] The present invention provides a multi-metal-based oxide electrocatalyst and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.
[0006] In order to achieve the above-mentioned purpose, an embodiment of the present invention provides a multi-metal-based oxide electrocatalyst and a preparation method and application thereof. The specific method is: first, five metal salt solutions are uniformly mixed by ultrasound, an organic ligand containing a specific substituent is added to the uniformly mixed solution, and stirred at room temperature for a certain period of time, followed by centrifugation and freeze-drying, and the freeze-dried sample is rapidly heated and cooled, and then the sample is ground to finally obtain a multi-metal-based oxide electrocatalyst. The catalyst obtained by the rapid annealing and regulation of the crystal phase distribution technology of the multi-metal-based oxide has the advantages of adjustable crystal structure, good conductivity, diverse catalytic active sites, rich multi-level structure and pore size distribution, and thus exhibits better oxygen evolution activity and stability than the commercial catalyst IrO2. As a highly active and stable water electrolysis oxygen evolution electrode, it has broad industrial application prospects.
[0007] The present invention provides a method for preparing a multi-metal-based oxide electrocatalyst, comprising the following steps:
[0008] S1, adding the metal salt to the solvent, and mixing uniformly by ultrasonication to obtain a mixed solution;
[0009] S2, adding an organic ligand containing a specific functional group to the mixed solution, stirring at room temperature, and sequentially centrifuging and freeze-drying to obtain a precursor powder;
[0010] S3, placing the precursor powder in a tube furnace and calcining it under a protective atmosphere;
[0011] S4. Ball milling the calcined sample to obtain the multi-metal-based oxide electrocatalyst.
[0012] According to one aspect of this embodiment, in step S1, the metal in the metal salt includes chromium, manganese, iron, cobalt, and nickel; wherein the molar ratio of chromium, manganese, iron, cobalt, and nickel is (1-3):(1-3):(1-3):(1-3):(1-3); and the solvent is water or ethanol. More preferably, the metal salt is nitrate; the molar ratio of chromium, manganese, iron, cobalt, and nickel is 1:1:1:1:1; and the solvent is ethanol.
[0013] According to one aspect of this embodiment, in step S1, the ultrasonic treatment time is 30 minutes.
[0014] According to one aspect of this embodiment, in step S2, the organic ligand is selected from at least one of 2,3-dihydroxybenzoic acid, thiophenol, and phenol, and the molar ratio of the organic ligand to the metal in the metal salt is 1:1 to 3:1.
[0015] According to one aspect of this embodiment, in step S2, the stirring instrument is selected from a magnetic stirrer or a mechanical stirrer, and the stirring time is 8 to 12 hours.
[0016] More preferably, the organic ligand is 2,3-dihydroxybenzoic acid, the molar ratio of the organic ligand to the metal in the metal salt is 1:1, the stirring instrument is a mechanical stirrer, and the stirring time is 12 hours. The stirring treatment is to allow the organic ligand to fully react with the metal ion, and the stirring instrument is preferably a mechanical stirrer to avoid the magnetic field affecting the uniform mixing of the organic chelate.
[0017] According to one aspect of the present embodiment, in step S3, the protective atmosphere is argon; the heating rate is 5 to 30°C / min, the calcination temperature is 600 to 1000°C, and the holding time is 0 to 4h. More preferably, under an argon atmosphere, the temperature is raised to 600 to 1000°C at a rate of 20°C / min without holding time, and then naturally cooled to room temperature. In this process, the heating rate of 20°C / min and no holding time are used to make the dominant unit cell grow rapidly and form a stable crystal structure without being disturbed by the diffusion of other metal ions.
[0018] According to one aspect of this embodiment, in step S4, the ball milling speed is 200-500 r / min, and the ball milling time is 2-5 h. Since the ball milling speed is too high and the time is too long, the structure of the material itself will be destroyed, thereby affecting the catalytic performance and stability of the material. More preferably, the ball milling speed is 300 r / min, and the ball milling time is 3 h.
[0019] Based on a general inventive concept, an embodiment of the present invention provides a multi-metal-based oxide electrocatalyst obtained by the above preparation method.
[0020] The embodiments of the present invention also provide the use of the multi-metal-based oxide electrocatalyst obtained by the above-mentioned preparation method in the electrolytic oxygen evolution reaction.
[0021] According to one aspect of this embodiment, the multi-metal-based oxide electrocatalyst is made into a slurry and coated on a conductive substrate to prepare a multi-metal-based oxide electrode; the conductive substrate is selected from one of carbon paper, nickel foam, and titanium mesh. More preferably, the conductive substrate is nickel foam.
[0022] The above scheme of the present invention has the following beneficial effects:
[0023] (1) The present invention proposes for the first time to use 2,3-dihydroxybenzoic acid as an organic ligand to prepare a multi-metal oxide electrocatalyst. In the metal organic framework structure formed by metal ions and 2,3-dihydroxybenzoic acid, the conjugation effect formed between the carbonyl carbon and the hydroxyl oxygen in the molecular structure of 2,3-dihydroxybenzoic acid will cause the electron density to be redistributed between the carbonyl carbon and the hydroxyl oxygen, thereby weakening the carbonyl carbon's ability to attract electrons, and then leading to different coordination abilities between the two and the metal ions, which is conducive to further structural modification and improvement. Based on the structural characteristics of the selected organic ligand, the appropriate pyrolysis conditions can be selected to regulate the diffusion rate of the metal ions, so that they diffuse to the appropriate position to form a unit cell and grow rapidly, and finally form a stable crystal structure. In heterogeneous catalysts, the performance of the catalyst is closely related to its crystal structure. Therefore, the crystal structure distribution of the catalyst is adjusted by temperature to form a heterogeneous structure with optimal OER catalytic activity. This adjustment method is simple and efficient. It can be applied to the field of electrocatalytic reactions and is easy to mass produce.
[0024] (2) The catalyst synthesized by the present invention exhibits a FeCo / Cr 0.5 Mn 1.5 NiO4 heterostructure, in which FeCo(111) crystal plane and Cr 0.5 Mn 1.5 The heterogeneous structure formed by NiO4 causes the electronic interaction at the heterogeneous interface to induce charge redistribution, and the change in electronic structure optimizes the adsorption strength of different adsorption sites of the catalyst to the reaction intermediates. Thanks to this, the catalyst exhibits efficient and stable OER performance in alkaline media.
[0025] (3) The catalyst synthesized by the present invention presents a layered structure, which shows a higher specific surface area than a dense block structure, thereby increasing the exposure of catalytic active sites, helping to improve the activity and efficiency of the catalytic reaction. In addition, the layered structure is conducive to the diffusion and transmission of reactants and products, and can reduce the agglomeration and loss of active components to a certain extent, further improving the stability of the catalyst. In addition, compared with other multi-metal catalysts, the catalyst of the present invention has high purity, good dispersibility, rich multi-level structure and pore size distribution, and exhibits excellent catalytic activity and stability in the application of oxygen evolution reaction, and is suitable for large-scale production.
[0026] (4) The multi-metal oxide catalyst prepared by the present invention exhibits excellent catalytic performance and outstanding stability when applied to oxygen evolution reaction. 2 , 50mA / cm 2 When the overpotential of the electrocatalytic oxygen evolution reaction is 280mV and 339mV respectively, after 5000 CV cycles, there is no obvious shift in the LSV curve before and after the cycle, which shows excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 are scanning electron microscope images of multi-metal oxides (MOs) according to embodiments of the present invention, wherein (a) is MOs-600, (b) is MOs-700, (c) is MOs-800, (d) is MOs-900, and (e) is MOs-1000;
[0029] Figure 2 is an X-ray diffraction pattern of a multi-metal oxide according to an embodiment of the present invention;
[0030] Figure 3 is an OER activity test curve of the multi-metal oxide of the embodiment of the present invention;
[0031] Figure 4 This is a comparison diagram of the OER polarization curves at the 1st cycle and the 5000th cycle after the stability is tested by cyclic voltammetry in Example 3 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0033] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0035] In view of the existing problems, the present invention provides a multi-metal-based oxide electrocatalyst and a preparation method and application thereof.
[0036] Example 1
[0037] This embodiment protects a method for preparing a multi-metal-based oxide electrocatalyst.
[0038] The method of this embodiment specifically includes the following steps:
[0039] (1) 2 mmol each of manganese nitrate, nickel nitrate, iron nitrate, cobalt nitrate, and chromium nitrate were dissolved in 60 mL of ethanol by ultrasonication for 30 min;
[0040] (2) adding 10 mmol of 2,3-dihydroxybenzoic acid to the sonicated solution, stirring the solution with a mechanical stirrer for 12 h, and then centrifuging and freeze-drying the solution;
[0041] (3) The freeze-dried sample was placed in a tube furnace, heated to 600 °C at a rate of 20 °C / min without holding time under argon atmosphere, and then naturally cooled to room temperature;
[0042] (4) ball milling the calcined sample to obtain a multi-metal oxide, wherein the ball milling speed is 300 r / min and the ball milling time is 3 h;
[0043] (5) 5 mg of the sample was weighed out using a balance and placed in a 3 mL centrifuge tube. Then, 350 μL of water, 150 μL of ethanol, and 40 μL of Nafion solution were added to the centrifuge tube to prepare a slurry, which was then coated on a nickel foam substrate to prepare a multi-metal oxide electrode.
[0044] The multi-metal oxide catalyst (MOs-600) prepared in this example has a layered structure ( Figure 1 ). By analyzing the X-ray diffraction pattern ( Figure 2 ), and found that when the temperature was raised to 600℃, no obvious crystallization peak appeared inside the material. The oxygen evolution reaction activity was tested, such as Figure 3 As shown, at a current density of 10 mA / cm 2, 50mA / cm 2 When the overpotential of the electrocatalytic oxygen evolution reaction is 318mV and 397mV, respectively, it is better than the commercial IrO2 catalyst (355mV@10mA / cm 2 、449mV@50mA / cm 2 ).
[0045] Example 2
[0046] This embodiment protects a method for preparing a multi-metal-based oxide electrocatalyst.
[0047] The method of this embodiment specifically includes the following steps:
[0048] (1) 2 mmol each of manganese nitrate, nickel nitrate, iron nitrate, cobalt nitrate, and chromium nitrate were dissolved in 60 mL of ethanol by ultrasonication for 30 min;
[0049] (2) adding 10 mmol of 2,3-dihydroxybenzoic acid to the sonicated solution, stirring the solution with a mechanical stirrer for 12 h, and then centrifuging and freeze-drying the solution;
[0050] (3) The freeze-dried sample was placed in a tube furnace, heated to 700 °C at a rate of 20 °C / min without holding time under argon atmosphere, and then naturally cooled to room temperature;
[0051] (4) ball milling the calcined sample to obtain a multi-metal oxide, wherein the ball milling speed is 300 r / min and the ball milling time is 3 h;
[0052] (5) 5 mg of the sample was weighed out using a balance and placed in a 3 mL centrifuge tube. Then, 350 μL of water, 150 μL of ethanol, and 40 μL of Nafion solution were added to the centrifuge tube to prepare a slurry, which was then coated on a nickel foam substrate to prepare a multi-metal oxide electrode.
[0053] The multi-metal oxide catalyst (MOs-700) prepared in this example has a layered structure ( Figure 1 ). By analyzing the X-ray diffraction pattern ( Figure 2 ), with the increase of calcination temperature, two broad peaks can be seen in the XRD spectrum of MOs-700, indicating that there are obvious crystallization peaks inside the material. Test its oxygen evolution reaction activity, such as Figure 3 As shown, at a current density of 10 mA / cm 2 , 50mA / cm 2 When the overpotential of the electrocatalytic oxygen evolution reaction is 287mV and 357mV, respectively, which is better than the commercial IrO2 catalyst (355mV@10mA / cm 2 、449mV@50mA / cm 2).
[0054] Example 3
[0055] This embodiment protects a method for preparing a multi-metal-based oxide electrocatalyst.
[0056] The method of this embodiment specifically includes the following steps:
[0057] (1) 2 mmol each of manganese nitrate, nickel nitrate, iron nitrate, cobalt nitrate, and chromium nitrate were dissolved in 60 mL of ethanol by ultrasonication for 30 min;
[0058] (2) adding 10 mmol of 2,3-dihydroxybenzoic acid to the sonicated solution, stirring the solution with a mechanical stirrer for 12 h, and then centrifuging and freeze-drying the solution;
[0059] (3) The freeze-dried sample was placed in a tube furnace, heated to 800 °C at a rate of 20 °C / min without holding time under argon atmosphere, and then naturally cooled to room temperature;
[0060] (4) ball milling the calcined sample to obtain a multi-metal oxide, wherein the ball milling speed is 300 r / min and the ball milling time is 3 h;
[0061] (5) 5 mg of the sample was weighed out using a balance and placed in a 3 mL centrifuge tube. Then, 350 μL of water, 150 μL of ethanol, and 40 μL of Nafion solution were added to the centrifuge tube to prepare a slurry, which was then coated on a nickel foam substrate to prepare a multi-metal oxide electrode.
[0062] The multi-metal oxide catalyst (MOs-800) prepared in this example has a layered structure ( Figure 1 ). By analyzing the X-ray diffraction pattern ( Figure 2 ), when the temperature rises to 800℃, obvious diffraction peaks can be observed. Compared with the standard cards (PDF#04-008-7199, PDF#04-002-3694, PDF#04-014-0165), it is found that the most obvious XRD diffraction peak (44.01°) corresponds to the FeCo(111) crystal plane. Test its oxygen evolution reaction activity, such as Figure 3 As shown, at a current density of 10 mA / cm 2 , 50mA / cm 2 When the overpotential of the electrocatalytic oxygen evolution reaction is 280mV and 339mV, respectively, which is better than the commercial IrO2 catalyst (355mV@10mA / cm 2 、449mV@50mA / cm 2 ). After 5000 CV cycles, if Figure 4As shown, there is no obvious shift in the LSV curve before and after the cycle, indicating its excellent stability.
[0063] Example 4
[0064] This embodiment protects a method for preparing a multi-metal-based oxide electrocatalyst.
[0065] The method of this embodiment specifically includes the following steps:
[0066] (1) 2 mmol each of manganese nitrate, nickel nitrate, iron nitrate, cobalt nitrate, and chromium nitrate were dissolved in 60 mL of ethanol by ultrasonication for 30 min;
[0067] (2) adding 10 mmol of 2,3-dihydroxybenzoic acid to the sonicated solution, stirring the solution with a mechanical stirrer for 12 h, and then centrifuging and freeze-drying the solution;
[0068] (3) The freeze-dried sample was placed in a tube furnace, heated to 900 °C at a rate of 20 °C / min without holding time under argon atmosphere, and then naturally cooled to room temperature;
[0069] (4) ball milling the calcined sample to obtain a multi-metal oxide, wherein the ball milling speed is 300 r / min and the ball milling time is 3 h;
[0070] (5) 5 mg of the sample was weighed out using a balance and placed in a 3 mL centrifuge tube. Then, 350 μL of water, 150 μL of ethanol, and 40 μL of Nafion solution were added to the centrifuge tube to prepare a slurry, which was then coated on a nickel foam substrate to prepare a multi-metal oxide electrode.
[0071] The multi-metal oxide catalyst (MOs-900) prepared in this example has a layered structure ( Figure 1 ). By analyzing the X-ray diffraction pattern ( Figure 2 ), when the temperature rises to 900℃, the XRD diffraction peak (44.94°) corresponding to the FeCo(110) crystal plane becomes sharper, while the XRD diffraction peak (44.01°) corresponding to the FeCo(111) crystal plane becomes weaker. Figure 3 As shown, at a current density of 10 mA / cm 2 , 50mA / cm 2 When the overpotential of the electrocatalytic oxygen evolution reaction is 313mV and 408mV, respectively, which is better than the commercial IrO2 catalyst (355mV@10mA / cm 2 、449mV@50mA / cm 2 ), indicating that the FeCo(111) dominant crystal plane and Cr can be regulated by temperature. 0.5 Mn 1.5NiO4 interacts with each other, thereby exhibiting higher OER catalytic activity.
[0072] Example 5
[0073] This embodiment protects a method for preparing a multi-metal-based oxide electrocatalyst.
[0074] The method of this embodiment specifically includes the following steps:
[0075] (1) 2 mmol each of manganese nitrate, nickel nitrate, iron nitrate, cobalt nitrate, and chromium nitrate were dissolved in 60 mL of ethanol by ultrasonication for 30 min;
[0076] (2) adding 10 mmol of 2,3-dihydroxybenzoic acid to the sonicated solution, stirring the solution with a mechanical stirrer for 12 h, and then centrifuging and freeze-drying the solution;
[0077] (3) The freeze-dried sample was placed in a tube furnace, heated to 1000°C at a rate of 20°C / min without holding time under argon atmosphere, and then naturally cooled to room temperature;
[0078] (4) ball milling the calcined sample to obtain a multi-metal oxide, wherein the ball milling speed is 300 r / min and the ball milling time is 3 h;
[0079] (5) 5 mg of the sample was weighed out using a balance and placed in a 3 mL centrifuge tube. Then, 350 μL of water, 150 μL of ethanol, and 40 μL of Nafion solution were added to the centrifuge tube to prepare a slurry, which was then coated on a nickel foam substrate to prepare a multi-metal oxide electrode.
[0080] The multi-metal oxide catalyst (MOs-1000) prepared in this example has a layered structure ( Figure 1 ). By analyzing the X-ray diffraction pattern ( Figure 2 ), when the temperature continues to rise to 1000℃, the XRD diffraction peak (44.94°) corresponding to the FeCo(110) crystal plane becomes sharper, while the XRD diffraction peak (44.01°) corresponding to the FeCo(111) crystal plane continues to weaken. Figure 3 As shown, at a current density of 10 mA / cm 2 , 50mA / cm 2 When the overpotential of the electrocatalytic oxygen evolution reaction is 335mV and 433mV, respectively, it is better than the commercial IrO2 catalyst (355mV@10mA / cm 2 、449mV@50mA / cm 2 ), further illustrating that Cr 0.5 Mn 1.5The heterostructure formed by NiO4 and FeCo (111) crystal plane has a better catalytic effect on OER.
[0081] Comparative Example 1
[0082] This comparative example refers to Example 3, except that the organic ligand 2,3-dihydroxybenzoic acid is replaced with 1,10-phenanthroline, and the other steps and parameters are the same as those in Example 3.
[0083] At a temperature of 800°C, compared with Example 3, the crystal structure corresponding to the XRD diffraction peak of the catalyst prepared in this comparative example changes. By comparing the standard card, it is found that the XRD diffraction peaks correspond to MnCr2O4, Fe 0.75 Ni 0.25 、Co7Fe3. The oxygen evolution reaction activity was tested at a current density of 10mA / cm 2 When the overpotential of the comparative example (368mV@10mA / cm 2 ) is much larger than Example 3 (280mV@10mA / cm 2 ), indicating that the Cr 0.5 Mn 1.5 The heterostructure formed by NiO4 and FeCo alloy plays a key role in electrocatalytic OER.
[0084] Comparative Example 2
[0085] This comparative example refers to Example 3, except that the organic ligand 2,3-dihydroxybenzoic acid is replaced with benzoic acid, and the other steps and parameters are the same as those in Example 3.
[0086] At a temperature of 800°C, compared with Example 3, the crystal structure corresponding to the XRD diffraction peaks of the catalyst prepared in this comparative example changes. By comparing with the standard card, it is found that the XRD diffraction peaks correspond to Cr 0.5 Mn 1.5 NiO4 and FeCo, among which the diffraction peak intensity corresponding to the FeCo (200) crystal plane is the largest. The oxygen evolution reaction activity was tested at a current density of 10 mA / cm 2 The oxygen evolution overpotential is 335 mV, compared with Example 3 (280 mV @ 10 mA / cm 2 ) overpotential increases, indicating that only by selecting organic ligands containing specific functional groups can the dominant crystal plane of FeCo alloy and Cr be regulated by temperature. 0.5 Mn 1.5 NiO4 forms a heterostructure with optimal OER catalytic activity.
[0087] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a multi-metal-based oxide electrocatalyst, characterized in that: The steps include: S1, adding the metal salt to the solvent, and mixing uniformly by ultrasonication to obtain a mixed solution; S2, adding an organic ligand containing a specific functional group to the mixed solution, stirring at room temperature, and sequentially centrifuging and freeze-drying to obtain a precursor powder; S3, placing the precursor powder in a tube furnace and calcining it under a protective atmosphere; S4. Ball milling the calcined sample to obtain the multi-metal-based oxide electrocatalyst.
2. The method for preparing a multi-metal-based oxide electrocatalyst according to claim 1, characterized in that: In step S1, the metals in the metal salt include chromium, manganese, iron, cobalt and nickel; wherein the molar ratio of chromium, manganese, iron, cobalt and nickel is (1-3):(1-3):(1-3):(1-3):(1-3); and the solvent is water or ethanol.
3. The method for preparing a multi-metal-based oxide electrocatalyst according to claim 1, characterized in that: In step S1, the ultrasonic treatment time is 30 to 60 minutes.
4. The method for preparing a multi-metal-based oxide electrocatalyst according to claim 1, characterized in that: In step S2, the organic ligand is selected from at least one of 2,3-dihydroxybenzoic acid, thiophenol, and phenol, and the molar ratio of the organic ligand to the metal in the metal salt is 1:1 to 3:
1.
5. The method for preparing a multi-metal-based oxide electrocatalyst according to claim 1, characterized in that: In step S2, the stirring instrument is selected from a magnetic stirrer or a mechanical stirrer, and the stirring time is 8 to 12 hours.
6. The method for preparing a multi-metal-based oxide electrocatalyst according to claim 1, characterized in that: In step S3, the protective atmosphere is argon; the heating rate is 5-30°C / min, the calcination temperature is 600-1000°C, and the insulation time is 0-4h.
7. The method for preparing a multi-metal-based oxide electrocatalyst according to claim 1, characterized in that: In step S4, the ball milling speed is 200-500 r / min, and the ball milling time is 2-5 h.
8. A multi-metal-based oxide electrocatalyst obtained by the preparation method according to any one of claims 1 to 7.
9. Use of a multi-metal-based oxide electrocatalyst obtained by the preparation method according to any one of claims 1 to 7 in an electrolytic oxygen evolution reaction.
10. The use according to claim 9, characterized in that: The multi-metal-based oxide electrocatalyst is made into a slurry and coated on a conductive substrate to prepare a multi-metal-based oxide electrode; the conductive substrate is selected from one of carbon paper, nickel foam, and titanium mesh.
Citation Information
Patent Citations
Preparation method and application of multi-metal oxide nano material
CN110240189A
MANUFACTURING METHOD FOR OXYGEN EVOLUTION REACTION CATALYST COMPRISING Ru-Co OXIDES BY AEROSOL PYROLYSIS
KR102291269B1